Variation in leaf xeromorphism in the desert palm genus Washingtonia (Arecaceae). (March 2021) - Pérez, Vanessa; Arévalo, Andrea; Villanueva-Almanza, Lorena; Ezcurra, Exequiel
Abstract: Washingtonia palms occur scattered in oases and canyons of the larger Sonoran Desert from lat. 24° to lat. 34° N. Northern oases have an arid temperate climate while those in the south experience seasonally dry, tropical conditions. A marked latitudinal cline in morphological characters has been described within the genus. We hypothesized that aridity-adapted leaf traits in Washingtonia palms, such as amphistomaty and isolaterality, could exhibit a predictable trend along the 1300-km-long gradient, allowing us to test whether the evolution of leaf xeromorphism is correlated with environmental aridity. We took measurements of anatomical and functional traits of leaves in 16 oases spanning the whole distributional range of the genus in Mexico and the US. Using regression models, we examined the response of specific leaf area, leaf greenness, ẟ 13 C, stomatal size, and stomatal density to latitude, site, and landform. We used Principal Components Analysis and correlation matrices to identify bioclimatic variables that might be playing a role in the observed latitudinal patterns. Palms at northern sites have waxy, glaucous, thick, leaves and exhibit xeromorphic traits such as amphistomaty and isolaterality. Palms at more tropical sites have glossy green, thin leaves that do not show xeromorphic traits. Leaf xeromorphism, a morphological and physiological syndrome in Washingtonia palms, increases with aridity. Highlights: The larger Sonoran Desert exhibits an environmental gradient where two species of Washingtonia palms occur. Palms at northern, arid sites exhibit evident xeromorphic traits like amphistomaty and isolaterality. Palms at more tropical sites have leaves that do not show xeromorphic traits. Leaf xeromorphism constitutes a syndrome in Washingtonia palms. The evolution of leaf xeromorphism is correlated with increasing environmental aridity.